Social Mixed Policy in the Transformation of Low-Income Housing Areas: The Case of Fikirtepe - Bulbul Akin, Basak; Turkun, Asuman (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
In the post-1990 period when globalization and neoliberal policies dominated, new urban and social policies were developed to combat increased poverty, the strategies for the transformation of cities and interventions for low-income housing areas have changed, different approaches to low-incomes in housing policies have come up for the solution of social problems. Among these approaches, the social mix policy which is effective in many European and US cities has an important place. According to this approach; poverty is concentrated in low-income housing areas associated with low-income, unemployment and crime, thereby the socio-spatial segregations are deepening. Therefore, it was aimed to prevent these problems by restructuring and reconstructing the social housing which is the habitat of the low-incomes, arranging these areas to live together with the low and middle-income people. In Turkey, this perspective of urban transformation approach and rhetoric became prominent in the 2000s. The phenomenon of urban transformation that constitutes Turkey's most important agenda after 1999 Marmara Earthquake is dealt with the approach of integrating habitats of different socio-economic groups within the framework of social policy mix in the upper-scale plans, ensuring social cohesion and is similar to the developments in the world in terms of results. In this study, the context, objectives, implementation and results of social mix policy will be analyzed, establishing a relationship with the urban transformation in Turkey, Fikirtepe Urban Transformation Project Area identified as a case study will be discussed in private. Within this policy supported by discourses in the study area such as risk of disaster, unhealthy living conditions and security, the extent to which the transformation strategy for different income groups living together in the transformation implementation, the needs and demands of all income groups are taken into consideration and whether the project can produce solutions to socio-economic problems will be examined.
Keywords: Low-income housing areas; Fikirtepe; urban transformation; social mixed policy; GENTRIFICATION; NEIGHBORHOODS; Architecture